Discriminatory taxation of investment funds in the European Union: How the CJEU Case-law keeps ignoring neutrality - Ana Paula Dourado; Jessica Müller; Leidson Rangel; Christoph Spengel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
This paper examines the legal consequences and assesses the economic impact of the differing tax treatment of investment funds in Portugal, Germany, and Luxembourg before and after the Allianzgi-Fonds case decision. Before the Allianzgi-Fonds case decision the Portuguese investment taxation discriminated against foreign investments by levying a withholding tax compared to domestic ones. As a result of the Allianzgi- Fonds landmark case, our paper examines whether the Portuguese CIT-exemption extended to non-resident UCITS will lead to tax neutrality treatment of investment funds in the EU. Overall, we confirm that the abolishment of the discriminatory withholding tax can considerably reduce the effective tax levels for cross-border investments. Moreover, the abolishment also diminishes the domestic investment bias. Nonetheless, the results do not confirm the achievement of neutrality.
Keywords: H24; H25; K34; 330; European Court of Justice; Funds; Investor; Taxation; Portugal